Fate of Plant Available Nutrients during Hydrothermal Carbonization of Digestate1. Issue 12 (11th August 2015) - Funke, Axel
Abstract: Products from the hydrothermal carbonization of two digestates have been analyzed in order to investigate the fate of nitrogen, phosphorus, and potassium in specific plant available speciations. The availability of phosphate and potassium ions was significantly increased due to hydrothermal carbonization of a nutrient‐rich digestate. In contrast, the availability of NH4 + and PO4 3− in the process liquor was decreased to < 10 % of the original value in the case of a nutrient‐poor digestate. With the exception of nitrate, process parameters did not show an influence on the recovery of the investigated ions with the HTC process liquor. Abstract : Major nutrients are maintained during hydrothermal carbonization and their availability for plants can even be increased in some cases. This opens up new potential to convert nutrient rich biomass to solid fuels while recovering important nutrients with the process liquor at the same time to maintain local nutrient cycles.